Targeting mTOR signaling pathways and related negative feedback loops for the treatment of acute myeloid leukemia - Carneiro, Benedito A (Cancer Biol Ther, 2015)
An accumulating understanding of the complex pathogenesis of acute myeloid leukemia (AML) continues to lead to promising therapeutic approaches. Among the key aberrant intracellular signaling pathways involved in AML, the phosphatidylinositol 3-kinase/AKT/mammalian target of rapamycin (PI3K/AKT/mTOR) axis is of major interest. This axis modulates a wide array of critical cellular functions, including proliferation, metabolism, and survival. Pharmacologic inhibitors of components of this pathway have been developed over the past decade, but none has an established role in the treatment of AML. This review will discuss the preclinical data and clinical results driving ongoing attempts to exploit the PI3K/AKT/mTOR pathway in patients with AML and address issues related to negative feedback loops that account for leukemic cell survival. Targeting the PI3K/AKT/mTOR pathway is of high interest for the treatment of AML, but combination therapies with other targeted agents may be needed to block negative feedback loops in leukemia cells.